Tax Analysis Of Restaurants (PBJT) On Food And Beverages In Medan City In 2024 - Fanny Trisyah Dwi Putri; Natasya Panggabean; Vanisya Aprilia Sidauruk; Renny Maisyarah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the implementation of the Specific Goods and Services Tax (PBJT) for food and beverages or restaurant tax in Medan City after the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments. The study was conducted using a descriptive qualitative approach with document study and field observation methods. The results of the study show that the PBJT rate of 10% is in accordance with the provisions, but its implementation is still hampered by low compliance in reporting turnover and limited digital monitoring. The recommendations given are to increase the installation of digital transaction recording devices (tapping boxes), conduct tax socialization, and impose stricter sanctions.